Evaluation Study of Health Promotion Hospital (HPH) in Muhammadiyah Hospital in DKI Jakarta, Indonesia - Tatang, Emma Rachmawati; Mawartinah, Tri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Health Promotion in Hospital (HPH) initiatives still run slowly. This study aimed to evaluate the implementation of HPH at Muhammadiyah Hospital in Jakarta, Indonesia. The survey was carried out during March-April 2018 to 304 permanent employees in three Muhammadiyah Hospitals in Jakarta. Measurements include employee characteristics and self-assessment tools related to the achievement of HPH national standards. According to HPH activities, the results showed that the average knowledge of employees was good enough (5.6; max: 10) and good attitudes (29.6, max: 40), but low HPH activities (25.3%), and low involvement in HPH training (13.5%). The highest achievement was the Ã¢â‚¬Å“partnershipÃ¢â‚¬Â standard (68%), and the lowest achievement was Ã¢â‚¬Å“reviewing the needs of the hospital communityÃ¢â‚¬Â (50%). There were 56% of respondents stating the achievement of the HPH national standard in Muhammadiyah Hospital was good. The results of this study as evidence-based to design the priority of HPH improvement strategies in Muhammadiyah Hospital.